Intake and growth performance of Brahman and Boran crossbred heifers fed on optimized ash-based vitamin-mineral winter block with bentonitic clay binders - Rachel Mutore; James Madzimure; Irvin D.T. Mpofu; Courage Bangira (Aceh Journal of Animal Science, 2022)
Though use of cement as a binder has produced acceptable results in the manufacture of feed block, there are questions on the possible negative health effects and high cost associated with the use of building cement in the production of feed blocks. The objective of the study was to compare supplementation effect of cement and bentonite + cement as binders in optimised ash-based winter blocks on feed intake, weekly weight gain and hair characteristics of beef cattle. Sixteen Brahman x Boran crossbred heifers with initial body weight of 250 ± 5kg were allocated to four treatments in a completely randomized design. Treatments based on the binder used in fabricating the optimized ash-based vitamin-mineral winter block were: cement agglutinated block, bentonite + cement agglutinated block, negative control (no supplement), and positive control (commercially available winter block). Animals were penned and fed on Rhodes grass (Chloris gayana) hay constituting 11% crude protein (CP); 8 MJ/kg DM for seventy days (dry season). Feed and supplement blocks were weighed daily animal weights were collected on weekly basis. Hair samples were measured at the beginning and end of the experiment. There was no significant difference in voluntary feed intake between bentonite + cement block and the positive control (P0.05). Block intake was significantly higher (P0.05) for the commercially available block (0.70±0.05kg/head/day) than in the cement agglutinated block (0.44±0.04 kg/head/day) and the bentonite + cement agglutinated block (0.49±0.04 kg/head/day). All animals that received supplement block had significantly higher weight gains than those that did not receive supplement (P0.05). There was no significant difference in hair length across all treatments (P0.05). Ash-based winter block agglutinated by a combination of cement and bentonite clay is a viable supplement which helps trim down amount of cement in feed blocks and improve animal performance. Use of the locally produced optimised ash-based vitamin-mineral block for nourishing ruminant animals is highly recommended.